Analysis and algorithm of operating logistic expenses measuring of the universal logistic systems - T.V. Shcholokova (Marketing i Menedžment Innovacij, 2014)
The aim of the article. The aim of the article consists in creation of technology of the logistic operations adjusting of universal logistic system functioning that is made by structural categories of logistic operating expenses. The results of the analysis. Totality of methods and technologies of the quantitative measuring of logistic expenses is a component part of management methodology by logistic expenses (ULS – M – TVS), pre-condition of creation of that was determination within the framework postneoinstitutional of economic theory of fundamental concept of compatible enterprise in form the universal logistic system (ULS). Logic of methodology creation of ULS – M – TVS supposed formal division of logistic expenses in activity of ULS in two classes: class of infrastructural expenses (l-expenses) and class of operating expenses (а-expenses). Thus, corresponding analytical constructions was conducted in terms of logistic ERC-conception (conceptions of economic registration certificate) taking into account the strict provisions of axiomatic theory of economic analysis (АТЕА). The basic idea of creation of logistic ERC-conception was position that any products are produced in the corresponding universal logistic system (ULS) that is a simple or ramified global chain of financially-productive relationships with clear administrative relations. Thus, the priority function of the universal logistic system is transformation of material stream by means of totality of certain actions – logistic operations, and strategy of logistic management of arbitrary ULS must answer the next requirements of competition market: firstly, its presence of flexible informative base of total expenses of ULS, and, secondly, it is effective transactional politics the decouplig of that spreads to all centers of forming of operating logistic expenses. The process of collection of information about logistic expenses is difficult enough and depends foremost on that, will realize an enterprise the economic functions in composition integrated logistic system or operates independently as a subject of market relations. Those enterprises that are incorporated in the universal logistic system (ULS) take advantage in a modern global economy. So, research of issues of the day of economic theory must conduct in terms of the universal logistic system with the use of generals of methodology of management by logistic expenses ULS – M – TVS. In arbitrary ULS the key object of control is an order of consumer (strategic mediator) and operating under this ordering fulfillment. The cost accounting on processes (order, services, foods) allows to define a profit got at this ordering fulfillment margin, show, as the expenses related to maintenance of this consumer are formed, what stake and them each of centers of responsibility. We hide character; the specific of forming of the informative system about the logistic expenses of enterprise consists of necessity of exposure of all expenses, conditioned by concrete logistic processes, and also in grouping expenses not round the centers of responsibility, and round works and operations that take in resources. It should be noted that modern methods of management it is actively developed logistic expenses - new directions, algorithms and tools of adjusting of expenses, appear. Thus, base, axiomatic, necessary for the use there are next methods: method of normative expenses, method of determination of expenses on processes, method of determination of expenses taking into account the period of appeal of supplies, method of strategic management by expenses. Thus, the special analytical model as logistic technology of management operating logistic expenses cannot without the account of base methods be characterized as a key competense of main logistic management of ULS. Conclusions and directions of further researches. Within the framework of methodology of management by logistic expenses (ULS – M – TVS) that accompany functioning of the arbitrary universal logistic system with the diversificational market of sale, is formed transactional general act of sales on the basis of transactional of local laws of sales, that assisted creation of algorithmic vehicle of the quantitative measuring of operating of logistic expenses (а-expenses) taking into account the flowsheets of transformation of assets in the process of motion of raw material, material, labour, financial and informative streams on the logistic channel of compatible enterprise. The problem of harmonization of matrix global law of deliveries is investigational with the general act of sales, essence of that consists of reduction of overnormative supplies of raw material, WIP and prepared products in specialized centers of responsibility of ULS.